Everything Will Be Decided in Syria - Férez Gil, Manuel (The Copernicus Journal of Political Studies, 2018)
It is difficult to understand the current situation in Syria without making an analysis of the historical reasons that have led to the country on the brink of collapse. This brief article intends to expose the lines of rupture of the Syrian regime as well as the regional and international importance of this conflict. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14763